ANALISIS KINERJA PENGELOLAAN DANA DESA DI DESA MOTODUTO - Radjak, Lukfiah Irwan; Lantowa, Felmi D; Suleman, Nurjana; Torana, Nopriyanto (Program Studi Akuntansi, 2023)
This research aims to determine the performance of the Motoduto Village Government in managing the Village Fund. This research used a qualitative approach and conducted interviews with 9 informants. The results indicated the overall performance indicators studied have not been implemented properly by the Village Government. It was also found the main factors that led to the absence of performance allocations and the existence of a non-budgetary in the Motoduto Village Government were productivity, responsiveness and accountability factors. It is recommended to the Motoduto Village Government, providing facilities that can accommodate aspirations, criticisms, or suggestions. For transparency of information about Village Funds, you can use media in the form of billboards placed in strategic places. For the quality of the Motoduto Village apparatus, the Government can plan routine programs/training that can support village financial management.